Guides to the City: Berlin Anthologies - Ulrike Zitzlsperger (Studies in 20th & 21st Century Literature, 2004)
Michael Lewitscharoff's Berlin-Paket (Berlin Package) first appeared in 2001; it invites readers to take a stroll through the city and promises "surprising revelations" about Berlin's architecture, culture and history…
Keywords: Michael Lewitscharoff; Berlin-Paket; Berlin Package; architecture; Berlin; Berlin architecture; Berlin culture; Berlin history